Severe vivax malaria in Eastern India - Mukherjee, Joydeep; Chakrabarty, Pradeep (Asian Journal of Medical Sciences, 2015)
Background: Conventionally, vivax malaria was called as benign malaria. But recent reports of severe vivax malaria were coming from different parts of the World. We studied to find out different attributes of patients, suffering from Plasmodium vivax to reveal some key pattern of severe vivax malaria. Methods: Retrospective, observational and cross-sectional study was conducted comprising first hundred malaria indoor cases in a tertiary hospital in Kolkata, India, having unstable transmission. Their various parameters were noted in MS-Excel software. Malaria species was identified and severe malaria cases were noted according to WHO criteria. Data was analysed with GraphPad Instat Software. Results: Among 57 vivax malaria cases, 16 (28.1%) were having severe malaria and among 32 falciparum malaria cases, 11 (34.4%) were having severe malaria; without significant difference between two species in incidence of severe malaria manifestations. Two (18.2%) patients suffering from mixed malaria had severe malaria. Jaundice was the commonest severe malaria manifestation. Conclusion: Incidence of severe vivax malaria was high. Severe malaria manifestations were present in vivax and falciparum cases, without significant difference. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12094 Asian Journal of Medical Sciences Vol.6(5) 2015 17-20